Translational study for stereotactic body radiotherapy against non-small cell lung cancer, including oligometastases, considering cancer stem-like cells enable predicting clinical outcome from in vitro data. (April 2023) - Saga, Ryo; Matsuya, Yusuke; Sato, Hikari; Hasegawa, Kazuki; Obara, Hideki; Komai, Fumio; Yoshino, Hironori; Aoki, Masahiko; Hosokawa, Yoichiro
Highlights: IMK model considering the radioresistant cancer stem cells (CSCs) enabled reproduce the cell survival. IMK model also enabled reproduce curative effects of stereotactic body radiotherapy (SBRT) for lung cancer. Considering CSCs was an important parameter to predict tumor control probability of SBRT. Abstract: Background: Curative effects of stereotactic body radiotherapy (SBRT) for non-small cell lung cancer (NSCLC) have been evaluated using various biophysical models. Because such model parameters are empirically determined based on clinical experience, there is a large gap between in vitro and clinical studies. In this study, considering the heterogeneous cell population, we performed a translational study to realize the possible linkage based on a modeling approach. Methods: We modeled cell-killing and tumor control probability (TCP) considering two populations: progeny and cancer stem-like cells. The model parameters were determined from in vitro survival data of A549 and EBC-1 cells. Based on the cellular parameters, we predicted TCP and compared it with the corresponding clinical data from 553 patients collected at Hirosaki University Hospital. Results: Using an all-in-one developed model, the so-called integrated microdosimetric-kinetic (IMK) model, we successfully reproduced both in vitro survival after acute irradiation and the 3-year TCP with various fractionation schemes (6–10 Gy per fraction). From the conventional prediction without considering cancer stem cells (CSCs), this study revealed that radioresistant CSCs play a key role in the linkage between in vitro and clinical outcomes. Conclusions: This modeling study provides a possible generalized biophysical model that enables precise estimation of SBRT worldwide.